The Effect of the Use of MAGICO Media (Active Magnetics for Games and Cognitive Interaction) on Changes in Understanding the Concept of Magnetism in Grade IV Elementary School Students - Hamna Khaula Tsabitah; Wati Sukmawati (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to examine the effect of using the MAGICO learning media (Active Magnet for Games and Cognitive Interaction) on improving fourth-grade elementary students’ understanding of magnetism concepts. The background of this research is based on the low level of student comprehension regarding attractive and repulsive forces, magnetic poles, and magnetic fields, which is often due to passive and non-exploratory conventional teaching methods. MAGICO was developed as an innovative, game- and exploration-based learning medium designed to actively engage students in understanding abstract concepts through activities such as magnetic mazes and force-attraction experiment boards. This research employed a quasi-experimental method with a control group and an experimental group design. The study involved 40 students divided into two groups: the experimental class used MAGICO, while the control class received conventional instruction. A conceptual understanding test was administered before and after the intervention as the primary research instrument. Statistical analysis revealed no significant difference between the two groups in improving conceptual understanding of magnetism. Although the experimental group showed an increase in average scores, the difference was not statistically strong enough to confirm the effect of the intervention. Several factors may have influenced these results, including the relatively short duration of the intervention, heterogeneous classroom conditions, varying levels of student participation, and differences in prior knowledge. Additionally, students may have needed more time to adapt to the new learning media. Nevertheless, the upward trend in the experimental group's scores—where 72% of students showed a significant improvement—indicates the potential of MAGICO as an effective learning tool. In contrast, although 77% of students in the control group also showed improvement, the depth and consistency of their understanding were less evident.